Desain dan Konsep Alat Pirolisis Sampah Rumah Tangga dengan Kajian Kelayakan Ekonomi - Siregar, Zufri Hasrudy; Mawardi, Mawardi; Yasir, Muhammad (Abdimas Indonesian Journal, 2024)
Household waste processing is greatly influenced by the culture, habits, and education of housewives as the vanguard of waste management. In Medan, in 2021, waste was recorded at 210.56 tons per year. One of the proposed solutions is pyrolysis technology to process organic waste into bio-oil, which also produces by-products such as coconut shell charcoal and tar. An economic feasibility analysis was conducted to see the potential of this business in Sleman, with a total income from bio-oil and by-products of IDR 1,095,000 and a monthly profit of IDR 168,750. Research shows that dry twigs produce bio-oil with higher yields and calorific values ​​than dry leaves. However, from the economic analysis, this business shows unpromising results with a BEP of 197.04 units/month, a B/C Ratio of 1.18, an ROI of 1.58%, and a POT of 5.28 years. Although it is currently not profitable, the potential of bio-oil as an alternative fuel will increase if fuel prices rise.